2008
DOI: 10.1890/07-0906.1
|View full text |Cite
|
Sign up to set email alerts
|

Terrestrial Habitat Selection and Strong Density‐dependent Mortality in Recently Metamorphosed Amphibians

Abstract: To predict the effects of terrestrial habitat change on amphibian populations, we need to know how amphibians respond to habitat heterogeneity, and whether habitat choice remains consistent throughout the life-history cycle. We conducted four experiments to evaluate how the spatial distribution of juvenile wood frogs, Rana sylvatica (including both overall abundance and localized density), was influenced by habitat choice and habitat structure, and how this relationship changed with spatial scale and behaviora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
55
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(58 citation statements)
references
References 46 publications
3
55
0
Order By: Relevance
“…We also showed that such microhabitat conditions lead to rapid water loss and high mortality in small-scale caging studies (Rothermel and Luhring 2005) and most likely provide the direct mechanism for reduced abundance demonstrated in many previous studies. Behavioral studies show that both juvenile and adult amphibians often avoid entering clearcuts when given a choice (Rittenhouse and Semlitsch 2006, Patrick et al 2008, Todd et al 2009; but see Graeter et al 2008). Using smaller-scale mechanistic studies, we found that retention of CWD helped reduce water loss and increase the survival of juveniles over short periods, especially in slash piles .…”
Section: Ecological Consequences and Mechanismsmentioning
confidence: 87%
See 2 more Smart Citations
“…We also showed that such microhabitat conditions lead to rapid water loss and high mortality in small-scale caging studies (Rothermel and Luhring 2005) and most likely provide the direct mechanism for reduced abundance demonstrated in many previous studies. Behavioral studies show that both juvenile and adult amphibians often avoid entering clearcuts when given a choice (Rittenhouse and Semlitsch 2006, Patrick et al 2008, Todd et al 2009; but see Graeter et al 2008). Using smaller-scale mechanistic studies, we found that retention of CWD helped reduce water loss and increase the survival of juveniles over short periods, especially in slash piles .…”
Section: Ecological Consequences and Mechanismsmentioning
confidence: 87%
“…However, the willingness to travel through clearcuts differed by region and species or stage. In Maine, both juvenile and adult amphibians traveled through clearcuts, and individuals settled for short periods (Patrick et al 2006(Patrick et al , 2008. In Missouri, adults traveled through clearcuts, but virtually no metamorphs traveled successfully through clearcuts.…”
Section: Ecological Consequences and Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a forest is not a homogenous environment for the newt. The quality of a forest as a migration route through terrestrial habitats varies due to natural variations in vegetation cover or as a result of forest management activities (Patrick et al 2008). …”
Section: Amphibians In Changing Worldmentioning
confidence: 99%
“…Patrick, Harper, Malcolm, Hunter, and Calhoun (2008) found that juvenile wood frogs (R. sylvatica) will choose to stay in high quality habitat at extremely high densities rather than shift to low quality habitat and as a result will experience high density-dependent mortality. Quality habitat must be provided to ensure individuals have sufficient environments for foraging, refuge, overwintering, dispersal between habitats (Guerry & Hunter, 2002;Semlitsch & Bodie, 2003) and to shift habitats in forested areas which have experienced disturbances ).…”
Section: Terrestrial Habitat Compositionmentioning
confidence: 99%